Relation of Caulerpa racemosa (Forsskål) J.Agardh, 1873 (Chlorophyta;Bryopsidales) with the benthic sessile organism diversity and potential use of Sacoglossan molluscs as biocontrol agents in Santa Cruz, Galapagos Islands - Franklin Terán; Verónica Crespo-Pérez; Wilson Iñiguez; William Bensted-Smith; Rosita Calderón; Inti Keith (Regional Studies in Marine Science, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Rediscovery of Rhizopsammia wellingtoni in Galápagos after two decades - Inti Keith; Terry Gosliner; Rebecca Albright (Marine Biology, 2025)

Novel mesophotic kelp forests in the Galápagos archipelago - Salome Buglass; Hiroshi Kawai; Takeaki Hanyuda; Euan Harvey; Simon Donner; Julio De la Rosa; Inti Keith; Jorge Rafael Bermúdez; María Altamirano (Marine Biology, 2022)

The Eastern Tropical Pacific Marine Corridor (CMAR): The Emergence of a Voluntary Regional Cooperation Mechanism for the Conservation and Sustainable Use of Marine Biodiversity Within a Fragmented Regional Ocean Governance Landscape - Sarah Ryan Enright; Ricardo Meneses-Orellana; Inti Keith (Frontiers in Marine Science, 2021)
The San Jose Declaration formally established the Eastern Tropical Pacific Marine Corridor (CMAR) in 2004, a voluntary regional cooperation mechanism created by the coastal States of Ecuador, Costa Rica, Colombia, and Panama in response to anthropogenic pressures in the Eastern Tropical Pacific, one of the most productive and biodiverse oceans in the world. This article will explain how, in the absence of a coherent, overarching regional ocean governance framework, these four coastal States came together to create a regional cooperation mechanism for the conservation and sustainable use of marine biodiversity in the Eastern Tropical Pacific. The key normative features of CMAR will be examined, as well as legal and governance challenges, such as its non-binding nature, large scale, limited sectoral engagement, and insufficient resources. The analysis will be couched within a discussion of the wider regional ocean governance framework, which remains fragmented, with gaps and overlaps in terms of membership, mandates and geographic coverage. Possibilities for integration, and the potential impact of a new treaty protecting biodiversity beyond national jurisdiction (BBNJ), will also be considered.

Correction to: Heat attenuation and nutrient delivery by localized upwelling avoided coral bleaching mortality in northern Galapagos during 2015/2016 ENSO - Bernhard Riegl; Peter W. Glynn; Stuart Banks; Inti Keith; Fernando Rivera; Mariana Vera-Zambrano; Cecilia D’Angelo; Jörg Wiedenmann (Coral Reefs, 2019)

Heat attenuation and nutrient delivery by localized upwelling avoided coral bleaching mortality in northern Galapagos during 2015/2016 ENSO - Bernhard Riegl; Peter W. Glynn; Stuart Banks; Inti Keith; Fernando Rivera; Mariana Vera-Zambrano; Cecilia D’Angelo; Jörg Wiedenmann (Coral Reefs, 2019)

Marine Dinoflagellate Assemblage in the Galápagos Marine Reserve - Olga Carnicer; Patricia De La Fuente; Antonio Canepa; Inti Keith; Eduardo Rebolledo-Monsalve; Jorge Diogène; Margarita Fernández-Tejedor (Frontiers in Marine Science, 2019)